Record of new host plants associated to the invasive mealybug species Paracoccus marginatus Williams and Granara de Willink (Hemiptera: Pseudococcidae) in the Center and Littoral regions of Cameroon - Simo, H.S.K.; Goergen, Georg E.; Tindo, M. (Springer, 2021)
The papaya mealybug (PM) is a known notorious polyphagous insect pest of many plant species and has always been found associated with a new host/s in newly invaded areas. This pest recently invaded West and Central Africa. Surveys were conducted randomly from July 2014 to May 2018 to determine the host range of this pest in the Center and Littoral regions in Cameroon. Plants infested by PM were recognized by the presence of black sooty mould, leaf deformation and/or chlorosis. A standard infestation scale was used to evaluate the infestation level on each plant. After collection, infested plants were pressed, dried and identified at the national Herbarium. A total of 52 plant species (only one undetermined) belonging to 23 families were found infested by PM associated with other mealybug or with two species of mealybugs with a percentage of (79.2%, N = 75) and (20.8%, N = 75) respectively. Two plant families (out of 23 identified) and 18 plant species (out of 52 infested) were reported as host plants for the first time. The Euphorbiaceae, Malvaceae and Solanaceae are the most infested families. In addition to plant species from its native zone (tropical America), PM has established new associations with plants from tropical Africa. Carica papaya and ten additional plants were categorized as favored hosts of P. marginatus. These results will be very useful to develop appropriate management options for PM in West and Central Africa.